"Ditto Heads": Do Conservatives Perceive Greater Consensus Within Their Ranks Than Liberals?. (September 2014) - Stern, Chadly; West, Tessa V.; Jost, John T.; Rule, Nicholas O.
In three studies, we examined (a) whether conservatives possess a stronger desire to share reality than liberals and are therefore more likely to perceive consensus with politically like-minded others even for non-political judgments and, if so, (b) whether motivated perceptions of consensus would give conservatives an edge in progressing toward collective goals. In Study 1, participants estimated ingroup consensus on non-political judgments. Conservatives perceived more ingroup consensus than liberals, regardless of the amount of actual consensus. The desire to share reality mediated the relationship between ideology and perceived ingroup consensus. Study 2 replicated these results and demonstrated that perceiving ingroup consensus predicted a sense of collective efficacy in politics. In Study 3, experimental manipulations of affiliative motives eliminated ideological differences in the desire to share reality. A sense of collective efficacy predicted intentions to vote in a major election. Implications for the attainment of shared goals are discussed.